Effectiveness of the Regional Government Information System (SIPD) implemented in the General Affairs Section of the Regional Secretariat of North Minahasa Regency - Pinontoan, Victor R.; Pangkey, Itje; Mamonto, Fitri H. (International Journal of Information Technology and Education, 2025)
This study investigates the effectiveness of the Regional Government Information System (SIPD) implementation in the General Affairs Section of the Regional Secretariat of North Minahasa Regency. SIPD, mandated by Permendagri No. 70/2019, aims to improve transparency, accountability, and efficiency in regional governance by integrating planning, budgeting, execution, reporting, and asset management processes. The primary objectives are to assess the operational performance of SIPD, identify factors inhibiting its effectiveness, and propose strategic recommendations for improvement. Using a qualitative descriptive approach, data were collected through in-depth interviews with key informants, including the Regional Secretary, Head of the General Affairs Section, Budget Treasurer, and SIPD Operators, direct observation of SIPD usage, and document analysis of SIPD reports and related regulatory frameworks. Data were analyzed following Miles and Huberman’s interactive model, encompassing data reduction, presentation, and verification through triangulation. Findings reveal that SIPD has substantially streamlined administrative and financial processes, enabling real-time access to budgetary data, reducing manual paperwork, and enhancing decision-making. However, constraints such as limited human resource capacity, intermittent infrastructural support, incomplete data integration, and resistance to change hinder optimal performance. Challenges arise from inadequate training, inconsistent internet connectivity, and unclear standard operating procedures. The study concludes that while SIPD holds significant potential for modernizing local governance, its efficacy is undermined by technical, human, and organizational barriers. Recommendations include targeted capacity-building programs, infrastructural upgrades, refinement of data protocols, and stronger leadership commitment to foster a culture of digital transformation. These measures are expected to enhance SIPD’s functionality, thereby elevating public service quality and accountability in North Minahasa Regency.